Morphological changes of the hip commonly associated with femoroacetabular impingement are not correlated with rotational range of hip motion in elite soccer athletes - Orlandi Bento, A.; Falótico, G.; Enseki, K.; Alves Cunha, R.; Ejnisman, B.; Arliani, G.; Cohen, M. (Sports Health: A Multidisciplinary Approach, 2021)
Background: Morphological changes characteristic of femoroacetabular impingement (FAI) are common in soccer players. However, the clinical relevance of such anatomical variations is still not well-defined. Hypothesis: We hypothesized that high alpha angle values and/or acetabular retroversion index (ARI) are correlated with rotational range of motion (ROM) of the hip and that there are clinical-radiological diferences between the dominant lower limb (DLL) and nondominant lower limb (NDLL) in professional soccer players. Study Design: Cross-sectional. Level of Evidence: Level 3. Methods: A total of 59 male professional soccer players (average age 25.5 years, range 18-38 years) were evaluated in the preseason. As main outcome measures, we evaluated the alpha angle and the ARI and hip IR and ER ROM with radiographic analysis. Results: The measurements taken on DLL and NDLL were compared and a significant difference was found between the sides in the ER (P = 0.027), where the DLL measures were 1.54° (95% CI, 0.18-2.89) greater than the NDLL. There were no significant differences between the sides in the measures of IR (P > 0.99), total ROM (P = 0.07), alpha angle (P = 0.250), and ARI (P = 0.079). The correlations between the rotation measurements and the alpha angle in each limb were evaluated and the coefficient values showed no correlation; so also between the ARI and rotation measures. Conclusion: Morphological changes of the femur or acetabulum are not correlated with hip IR and ER ROM in male professional soccer players. ER on the dominant side was greater than on the nondominant side. There was no significant difference in the other measurements between sides. Clinical Relevance: In clinical practice, it is common to attribute loss of hip rotational movement to the presence of FAI. This study shows that anatomical FAI may not have a very strong influence on available hip rotational movement in professional soccer athletes.